2022
DOI: 10.1136/neurintsurg-2022-018776
|View full text |Cite
|
Sign up to set email alerts
|

Associated genetic variants and potential pathogenic mechanisms of brain arteriovenous malformation

Abstract: BackgroundThe pathogenic mechanism of brain arteriovenous malformation (bAVM) is poorly understood. A growing body of evidence indicates that genetic factors play crucial roles in bAVM. This study examined genetic variants associated with bAVM through quantitative synthesis and qualitative description of literature.MethodsFive databases were searched to gather potentially relevant articles published up to January 2022. STATA 14.0 software was used for statistical analyses. Pooled odds ratios and 95% confidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 39 publications
(84 reference statements)
0
10
0
Order By: Relevance
“…VEGF is highly expressed in endothelial cells of bAVM, especially in ruptured bAVM lesions ( McDonald et al, 2015 ). Activation of this pathway could promote endothelial cell migration and recruitment of smooth muscle cells, resulting in pathological angiogenesis ( Liu et al, 2022 ). A recent study using mouse bAVM models demonstrated that an elevated VEGF level could contribute to bAVM hemorrhage by exposure to variable degrees of higher intraluminal flow and hypertension in the venous system ( Cheng et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…VEGF is highly expressed in endothelial cells of bAVM, especially in ruptured bAVM lesions ( McDonald et al, 2015 ). Activation of this pathway could promote endothelial cell migration and recruitment of smooth muscle cells, resulting in pathological angiogenesis ( Liu et al, 2022 ). A recent study using mouse bAVM models demonstrated that an elevated VEGF level could contribute to bAVM hemorrhage by exposure to variable degrees of higher intraluminal flow and hypertension in the venous system ( Cheng et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been reported that these genes can increase the expression of inflammatory cytokines in bAVM tissues, leading to endothelial dysfunction and malformation of vasculature (Krithika and Sumi, 2021). It has been shown that inflammatory infiltration can be observed even in unruptured bAVM lesions, proving the role of inflammation in the development and rupture of the disease (Liu et al, 2022). As the disease progresses, endothelial lesions would weaken the vasculature, and once patients are exposed to a trigger, an acute hemorrhage event occurs.…”
Section: Methodological Quality Assessmentmentioning
confidence: 99%
“…100 More than 1200 dysregulated genes have been identified in human bAVM tissue. 101,102 The functions of these genes are directly linked to inflammation, angiogenesis, vasculogenesis, cell migration, and the cytoskeletal system. 103…”
Section: Nonsurgical Treatment Modalitiesmentioning
confidence: 99%
“…Several pathogenic gene variants in the TGF-β pathway have been identified through genome-wide association studies (GWAS) and whole exome trio sequencing. These variants are linked to small vessel ischemic strokes, intracerebral hemorrhages, and sporadic brain arteriovenous malformations (AVMs) [110,111]. Increased expression of TGF-β1 has been found in the brain tissue after ischemic stroke, as well as in hereditary amyloidosis-Dutch type with cerebral hemorrhage [112].…”
Section: Tgf-𝜷𝟏/smad3 Signalling Play a Role In Col18a1 -/-Mice Ecm A...mentioning
confidence: 99%